The Relevance of Nusantara Culture Based Digital Learning to Support Character Building in Elementary School Students: A Literature Review - Berlian Hariratul Mahya; Anis Yuliani; Eko Handoyo; Indriana Eko Armaidi (Indo Publishing, 2026)
The rapid development of digital technology and the importance of preserving local culture encourage the integration of Nusantara cultural values into technology-based learning. This study aims to analyse the relevance of Nusantara culture-based digital learning in supporting character strengthening of elementary school students. The method used is a systematic literature review with data sources from scientific articles obtained through Google Scholar and traced using the Publish or Perish application. Out of 200 identified articles, 6 articles met the inclusion criteria (Indonesian language, full text, 2021–2026 publication year, focus on elementary school) and were systematically analysed using narrative synthesis. The results show that culture-based digital learning can improve cultural literacy, learning motivation, awareness of national identity, as well as character values such as love for the homeland, mutual cooperation, and environmental care. Furthermore, the integration of local culture in digital learning also introduces the potential of regional tourism from an early age. This study concludes that Nusantara culture-based digital learning is relevant to be applied to support sustainable character education in Indonesia.